Impact of quintessence and cloud of strings on self-consistent d-dimensional charged thin-shell wormholes - Arfa Waseem; Faisal Javed; M. Zeeshan Gul; G. Mustafa; Abdelghani Errehymy (European Physical Journal C: Particles and Fields, 2023)
Abstract This article evaluates the stability constraints of higher-dimensional geometry of thin-shell wormholes developed from the two equivalent copies of inner and outer d-dimensional charged anti-de Sitter black holes bounded by a cloud of strings and quintessence. Such geometrical structures are built using a cut-and-paste method that joins two identical forms of black hole solutions at the hypersurface. We develop the equation of motion for the constructed wormholes and then use the linear radial perturbation approach to examine the stable configuration. The stability constraints depend on the dimensions of the black holes, cloud, and quintessence parameters. It is worth mentioning that the possibility of a stable structure is greatest for the choice of d-dimensional charged anti-de Sitter black holes with quintessence and a cloud of strings.